A novel herbivorous wood-borer insect outbreak triggers die-offs of a foundation plant species in coastal ecosystems. Issue 1 (16th December 2020) - Ning, Zhonghua; Chen, Cong; Xie, Tian; Wang, Qing; Ma, Xu; Sui, Haochen; Cui, Baoshan
ABSTRACT: Introduction:Understanding the trophic interactions between plants and herbivorous insects is essential for managing the ecosystem health and sustainability in the context of climate change and anthropogenic disturbance. The Tamarix chinensis is a foundation plant species of salt marshes in northern China, which provides a variety of ecological functions and services in coastal ecosystems such as withstanding storm tide, conserving biodiversity, and preventing shoreline erosion. Outcomes: However, through long-term field observations, for the first time, we found that the health of this population has been suffering from the potential outbreak of a novel wood-borer insect ( Zeuzera leuconotum Butler ) under multiple stresses, contributing substantially to the degradation of the coastal salt marshes. Discussion and Conclusion: Therefore, there is urgent need and great significance to investigate the potential impact of this herbivorous wood-borer insects on health and sustainability of plant community in coastal ecosystems for in-depth understanding its degradation mechanisms.